2012
DOI: 10.4072/rbp.2012.2.01
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Cladaitina Maheshwari & Meyen, 1975 (cordaitalean pollen) from Uppermost Permian deposits of the Famatina Range, Central Western Argentina

Abstract: -A new cordaitalean pollen species of Cladaitina Maheshwari & Meyen, namely Cladaitina veteadensis is described from the Upper Permian strata of Argentina. The morphology of these dispersed pollen grains were studied using light and scanning electron microscopy. Detailed comparisons are made with similar commonly recorded sporae dispersae incertae sedis forms mainly recorded from other Late Permian palynofloras elsewhere. Cladaitina veteadensis sp. nov. constitutes a characteristic and common component of a ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…4G). They are very similar to Cladaitina Maheshwari & Meyen, which was found associated to Cladostrobus Zalessky, a putative reproductive organ of the Angaran Rufloriaceae (Maheshwari & Meyen 1975) and was also reported from palynological assemblages in Permian strata of Argentina and attributed to Cordaitales (Zavattieri & Gutiérrez 2012).…”
Section: Floristic Association and Paleoenvironmental Significancesupporting
confidence: 68%
“…4G). They are very similar to Cladaitina Maheshwari & Meyen, which was found associated to Cladostrobus Zalessky, a putative reproductive organ of the Angaran Rufloriaceae (Maheshwari & Meyen 1975) and was also reported from palynological assemblages in Permian strata of Argentina and attributed to Cordaitales (Zavattieri & Gutiérrez 2012).…”
Section: Floristic Association and Paleoenvironmental Significancesupporting
confidence: 68%
“…Gutiérrez et al (2011) studied the diverse palynological assemblage from the lowest exposures of the unit in the Sierra de Narváez, Catamarca Province, central-western Argentina. Later, Zavattieri and Gutiérrez (2012), Gutiérrez et al (2014) and Zavattieri et al (2017) reported palynofloras (in part) from the type section of the La Veteada Formation (previously known as La Yesera Formation) exposed at the eastern end (28° 34′ S; 68° 45′ W) of the Famatina Range, north La Rioja Province (Fig. 1.1).…”
mentioning
confidence: 99%
“…Remarks . Zavattieri and Gutiérrez (2012) described Cladaitina veteadensis having the exoexine ornamented mainly equatorially and distally by grana and small verrucae closely spaced, usually coalescent at their bases that may form rugulae of variable development and/or having appearance of an irregular and small negative reticulum. The specimens resemble Densipollenites magnicorpus Tiwari and Rana (1981); both species were described as pollen grains usually bigger than 100µm, with a dark subcircular central body and saccus, but the Indian species differs in its intrareticulate exoexine.…”
Section: Resultsmentioning
confidence: 99%
“…The specimens resemble Densipollenites magnicorpus Tiwari and Rana (1981); both species were described as pollen grains usually bigger than 100µm, with a dark subcircular central body and saccus, but the Indian species differs in its intrareticulate exoexine. Inaperturopollenites nebulosus Balme was considered by Zavattieri and Gutiérrez (2012) a probable synonym of C. veteadensis specimens without an internal body. Interestingly, I. nebulosus has been identified in several Early Triassic assemblages (Hankel 1993; Hermann et al 2012; Jha et al 2018).…”
Section: Resultsmentioning
confidence: 99%